ARTIFICIAL INTELLIGENCE IN ECONOMIC FEASIBILITY STUDIES - M.M. Hatem Jabr Atshan (Scholar Express Journals, 2025)
Artificial intelligence represents a true revolution in the fields of economic feasibility studies and financial analysis. It introduces the tools and technologies necessary to effectively implement these processes. This is achieved through the analysis of big data. It can also enhance the ability of companies and institutions to make informed and effective financial and economic decisions. Among the most important conclusions and recommendations reached by the researcher are: The economic feasibility study depends primarily on the amount of information and data obtained by those conducting the study and the extent of its accuracy. Future trends can be predicted and specific processes Which they prepare in the correct manner and in a manner that is .identified consistent with the current reality, and it is recommended that it is necessary to conduct economic feasibility studies for all investment projects, regardless .of their types, whether private or public, and their sizes, whether small or large This is due to its importance in avoiding the risk of making the wrong
Keywords: Artificial Intelligence; Dimensions of Artificial Intelligence